2015
DOI: 10.3758/s13414-015-0876-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in highly skilled visual perceptual-motor striking skill

Abstract: Expertise studies into visual perceptual-motor skills have mainly focused their investigation upon group comparisons rather than individual comparisons. This study investigated the pick-up of visual information to time weight transfer and bat kinematics within an exemplar group of striking sport experts using an in situ temporal occlusion paradigm. Highly skilled cricket batsmen faced bowlers and attempted to strike delivered balls, whilst their vision was either temporally occluded through occlusion glasses p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Our example highlights that individual differences profiles were aligned with constraints theory that predicts the skill goal can be achieved through interaction of individual, task and environmental constraints (Higgins, 1977;Newell, 1986). Accordingly, our findings are consistent with other studies that have used constraints theory to predict and report individual differences in relation to performance at a specific instance in time (Müller et al, 2015a) and improvement of performance due to practice (Chow et al, 2008). Therefore, our developed equation could quantify individual performance, which is underpinned by an interacting constraints theoretical framework.…”
Section: Discussionsupporting
confidence: 90%
“…Our example highlights that individual differences profiles were aligned with constraints theory that predicts the skill goal can be achieved through interaction of individual, task and environmental constraints (Higgins, 1977;Newell, 1986). Accordingly, our findings are consistent with other studies that have used constraints theory to predict and report individual differences in relation to performance at a specific instance in time (Müller et al, 2015a) and improvement of performance due to practice (Chow et al, 2008). Therefore, our developed equation could quantify individual performance, which is underpinned by an interacting constraints theoretical framework.…”
Section: Discussionsupporting
confidence: 90%
“…The driver controller is powered by six AAA batteries housed in a case and connected by a short cable to the driver controller. The driver controller, spectacle driver, and battery power supply are housed within a portable bag that is usually strapped to the participant (e.g., batter), with the vision occlusion spectacles being connected to the driver, as had been done in previous in-situ temporal occlusion studies (see, e.g., Müller et al, 2015).…”
Section: Instrumentsmentioning
confidence: 99%
“…Second, high-speed sports skills such as the cricket bowler's delivery action and ball flight occurs under 1 s. Delays due to the reaction time of the experimenter in depressing the timer button to correspond with a simultaneously observed bowler's kinematic event, as well as transmission of the signal to switch the spectacles from transparent to opaque, can be problematic in terms of the precise occlusion timing relative to a kinematic event. For example, manual triggering incurs a range of occlusion timing that is approximately 200-300 ms (see, e.g., Farrow & Abernethy, 2003;Müller, Brenton, Dempsey, Harbaugh, & Reid, 2015). Again, by means of an automated force plate trigger system, it has been reported that a cricket batsman's vision can be temporally occluded within a 50-ms range prior to or after ball release of a cricket bowler's action .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Psycho-physiological measures such as pupil diameter, inter-beat heart rate intervals, electromyography (EMG), and galvanic skin response may be recorded to examine changes in mental effort or stress/anxiety as a function of skill on the task (e.g., Vater, Roca, & Williams, 2015). Biomechanical measurement tools can also be employed to record kinetic and kinematic variables that give insight into movement planning and execution processes (e.g., Müller, Brenton, Dempsey, Harbaugh & Reid, 2015;Smeeton & Williams, 2012). Finally, various behavioural manipulations, such as dual-task paradigms, can be used to determine the type of processes engaged during anticipation and decision making (e.g., Mulligan, Lohse & Hodges, 2016a,b) or the cognitive and attentional load associated with a task or skill level (e.g., Broadbent, Causer, Williams, & Ford, in press).…”
Section: 2mentioning
confidence: 99%